Pemanfaatan By-Product dari Hasil Produksi Filet Ikan dalam Pembuatan Abon - Joni Iskandar; Herpandi Herpandi; Rodiana Nopianti (Universitas Sriwijaya, 2016)
The purposes of this research were to create a diversified product (shredded) made from bone of fish as an alternative on the utilization of by-product fishery products that was rich in calcium, and to know the chemical and sensory characteristics of shredded fish bones of snakehead (Channa striata), fish bones of mackerel (Scomberomorus commersoni), fish bones of machetes (Chirocentrus Dorab), and fish bones of putak (Notopterus notopterus). This research used a randomized block design with four treatments of different types of fish bone (A1 = Fish bones of snakehead, A2 = Fish bones of mackerel, A3 = Fish bones of machetes, A4 = Fish bones of putak). The parameters observed were chemical analysis (moisture content, ash, protein, fat, carbohydrates, calcium, and phosphorus) and sensory test that used hedonic test (appearance, colour, aroma, texture, and taste). The results showed that the treatment of the different types of fish bone significantly effect on levels of fat and phosphorus. The moisture content value of shredded fish bones were ranged from 3.16% - 4.93%, the ash content of 20.47% - 23.75%, the protein content of 5.66% - 8.04%, the fat content 15,13% - 24.54%, the carbohydrate content of 44.92% - 51.44%, the calcium content of 15.91% - 16.87%, the phosphorus content 7.48% - 12.29%, and a sensory test results on all attributes were ranged rather like to like. The best treatment based on test results was obtained in the treatment of sensory A2 (shredded mackerel fish bones).